Customer satisfaction and service quality of spa in Penang / Suria Sulaiman... [et al.] - Sulaiman, Suria; Mohd Asri, Dian Aszyanti Atirah; Azmi, Azila; Mohamad Khamis, Nor Fazllina (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
Spa and wellness tourism are one of the famous and competitive industries compared to the other industries in Malaysia. Recently, spa and wellness tourism has been rapid growth in this country in and this kind of service has been advocated due to health tourism packages. Customer that consumes a product or services from the spa industry required product or services that meet their expectations. However, lack of skill of the staff and discomfort ambiance can lead to the unsatisfaction towards the service quality and decrease the level of customer satisfaction in the spa. The objective of this research is to find a relationship between the service quality of staff and ambiance towards customer satisfaction in the spa. This research used a questionnaire survey in order to gather the data. 300 respondents took part in the survey which is conducted in Penang focusing at Batu Ferringhi area. Findings show that there is a relationship between service quality of staff and also ambiance towards customer satisfaction in the spa.